EKONOMI MARITIM & SUMBER DAYA MANUSIA INDONESIA - Lis Lesmini; Budi Purwanto (Institut Transportasi dan Logistik Trisakti, 2016)
Indonesia's economic success in the maritime sector have ups and downs, it is normal for the support of the local maritime economy, the maritime economy requires particular expertise in implementation, it is not simple, for example, the handling of ships in ports, may cause high cost economy if mismanaged. Based on the data on the number of schools and colleges based maritime, Indonesia is still difficult to independently manage the maritime economy, this is an indicator of Indonesian human resources of the maritime sector. With the analysis of research and development to generate a clear picture, the author tries to create a script to get the simple conclusion that can be understood reader